The Authority Differences of Notary and PPAT in Making of Land Deed Certificate - Tocko Haryanto; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this study is to analyze and explain the Authority of Notaries and PPATs in Making Land Deeds Based on Act No. 2 of 2014 concerning Notary Positions and Government Regulation Number 24 of 2016 concerning Regulations of PPAT Positions. To analyze and explain the legal position of the rights and obligations of a notary based on Act No. 2 of 2014 concerning the Position of a Notary and the legal position of the rights and obligations of a PPAT based on Government Regulation Number 24 of 2016 concerning the Regulation of the Position of a PPAT. The method used by the researcher is normative and The specifications in this study is descriptive. The sources and types of data in this study are secondary data obtained from literature studies related to the theory of authority and legal certainty. Based on the results of the study that the difference between the authority of a notary and a PPAT in making a land deed is the authority of a notary in making the land deed, namely the land deed that is outside the authority of the PPAT as stated in Article 2 paragraph (2) of PP Number 37 of 1998. The authority of the official making the land deed is still limited by various kinds of legislation. Legal Position Rights and Obligations of Notaries and Legal Positions Rights and Obligations of PPAT is the urgency of the right to deny a Notary lies in the obligation of the Notary to carry out the mandate of the UUJN. The position of the Land Deed Maker Official is as an authentic deed maker official, besides that PPAT (Land Deed Making Officer) is also referred to as a secret custodian of the deed (regarding the contents) that has been made in order to maintain the interests of the parties in the deed.